Combining Immunocytokine and Ex Vivo Activated NK Cells as a Platform for Enhancing Graft-Versus-Tumor Effects Against GD2+ Murine Neuroblastoma - Bates, Paul D.; Rakhmilevich, Alexander L.; Cho, Monica M.; Bouchlaka, Myriam N.; Rao, Seema L.; Hales, Joanna M.; Orentas, Rimas J.; Fry, Terry J.; Gilles, Stephen D.; Sondel, Paul M.; Capitini, Christian M. (Frontiers in Immunology, 2021)
Management for high-risk neuroblastoma (NBL) has included autologous hematopoietic stem cell transplant (HSCT) and anti-GD2 immunotherapy, but survival remains around 50%. The aim of this study was to determine if allogeneic HSCT could serve as a platform for inducing a graft-versus-tumor (GVT) effect against NBL with combination immunocytokine and NK cells in a murine model. Lethally irradiated C57BL/6 (B6) x A/J recipients were transplanted with B6 bone marrow on Day +0. On day +10, allogeneic HSCT recipients were challenged with NXS2, a GD2+ NBL. On days +14-16, mice were treated with the anti-GD2 immunocytokine hu14.18-IL2. In select groups, hu14.18-IL2 was combined with infusions of B6 NK cells activated with IL-15/IL-15Rα and CD137L ex vivo. Allogeneic HSCT alone was insufficient to control NXS2 tumor growth, but the addition of hu14.18-IL2 controlled tumor growth and improved survival. Adoptive transfer of ex vivo CD137L/IL-15/IL-15Rα activated NK cells with or without hu14.18-IL2 exacerbated lethality. CD137L/IL-15/IL-15Rα activated NK cells showed enhanced cytotoxicity and produced high levels of TNF-α in vitro, but induced cytokine release syndrome (CRS) in vivo. Infusing Perforin-/- CD137L/IL-15/IL-15Rα activated NK cells had no impact on GVT, whereas TNF-α-/- CD137L/IL-15/IL-15Ra activated NK cells improved GVT by decreasing peripheral effector cell subsets while preserving tumor-infiltrating lymphocytes. Depletion of Ly49H+ NK cells also improved GVT. Using allogeneic HSCT for NBL is a viable platform for immunocytokines and ex vivo activated NK cell infusions, but must be balanced with induction of CRS. Regulation of TNFα or activating NK subsets may be needed to improve GVT effects.